2001
DOI: 10.1086/320599
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick C Variant Detection by Altered Sphingolipid Trafficking and Correlation with Mutations within a Specific Domain of NPC1

Abstract: Niemann-Pick disease type C (NPC) is a fatal, autosomal recessive lipidosis characterized by lysosomal accumulation of unesterified cholesterol and multiple neurological symptoms, such as vertical supranuclear ophthalmoplegia, progressive ataxia, and dementia. More than 90% of cases of NPC are due to a defect in Niemann-Pick C1 (NPC1), a late endosomal, integral membrane protein that plays a role in cholesterol transport or homeostasis. Biochemical diagnosis of NPC has relied on the use of patient skin fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 33 publications
9
108
0
Order By: Relevance
“…Since identifi cation of the NPC1 gene, several studies have reported specifi c disease-causing mutations among different populations and ethnic groups ( 27,29,31,33,40,52,53 ). In the present study, the 52 patients that provided gene mutations ranged in age between 1.5 and 48.5 years and were at different stages and severity of disease.…”
Section: (N = 34) Nsmentioning
confidence: 74%
“…Since identifi cation of the NPC1 gene, several studies have reported specifi c disease-causing mutations among different populations and ethnic groups ( 27,29,31,33,40,52,53 ). In the present study, the 52 patients that provided gene mutations ranged in age between 1.5 and 48.5 years and were at different stages and severity of disease.…”
Section: (N = 34) Nsmentioning
confidence: 74%
“…In the NPC1 patients, 12 different mutations and nine different genotypes were identified. Eight of the mutations had been previously described: p.E1089K (3265G>A) (Sun et al 2001), p.F284Lfs*26 (c.852delT) (Fancello et al 2009), p. A1132P(c.3394G>C) (Mavridou et al 2014), del promoter region and exons 1-10 (Rodriguez-Pascau et al 2012), p. R1186H(c.3557G>A) (Carstea et al 1997), p.P1007A (c.3019C>G) (Greer et al 1999), p.Q92R(c.275A>G) (Ribeiro et al 2001), and p.S940L(c.2819C>T) (Greer et al 1999). The mutations p.A1132P(c.3394G>C) and the large deletion of the promoter region and of exons 1-10 have only been described in Greek patients (included in this report as #2, #3, #7).…”
Section: Resultsmentioning
confidence: 99%
“…The function of NPC1 is not fully understood, but NPC cells exhibit a trafficking defect at the late endosomal/lysosomal stage, as observed for cholesterol by using Filipin staining (32). Accumulation of Sph and lactosylceramide was previously visualized using fluorescent lipid analogs (33,34). Here, we used TFS to visualize Sph localization and trafficking.…”
Section: Subcellular Localization Of Lipids and Lipid-interacting Promentioning
confidence: 99%